Effect of Different Obturation Techniques on Sealer Penetration into Dentinal Tubules after Final Irrigation with XP-Endo Finisher File - Demir, Erhan (2023)
The first objective of this research was to evaluate the effectiveness of XP-Endo Finisher on dentinal tubule penetration of irrigation solution using confocal laser scanning microscopy. The main purpose of this research was to compare the effect of cold lateral condensation, continuous wave obturation and core-carrier based techniques on sealer penetration. Sixty mandibular premolars were prepared and allocated into two experimental groups (n=30) as the final irrigation technique and obturation technique experiment. In the final irrigation technique experiment, final irrigation was performed with XP-Endo Finisher, passive ultrasonic irrigation (PUI) and conventional needle irrigation (CNI) (n=10). The roots in the obturation technique experiment were also assigned into 3 groups and obturated with cold lateral condensation, continuous-wave obturation and core-carrier techniques (n=10). The most effective activation method, which emerged as a result of the first part of this study, was used as the final irrigation method in the obturation technique experiment. Then, all roots were sectioned in 1-mm-thick slices at 3mm from the apex for scanning. In terms of depth and percentage of material penetration, CNI exhibited significantly the lowest values and no significant difference was found between others. Also, there was no significant difference among obturation methods. In conclusion, XP-Endo Finisher and PUI are more effective than CNI on irrigant penetration. Sealer penetration into dentinal tubules is independent of obturation techniques.